1981
DOI: 10.4315/0362-028x-44.12.896
|View full text |Cite
|
Sign up to set email alerts
|

Production of Botulinum Toxin in Inoculated Pack Studies of Foil-Wrapped Baked Potatoes

Abstract: Idaho Russet Burbank potatoes were surface or stab inoculated with 10 to 105 spores of Clostridium botulinum type A strain, overwrapped in aluminum foil, baked at 204 C for 50 min or 96 C for 3 h and then held at 22 or 30 C. The shortest incubations resulting in the first botulinogenic potatoes were inversely related to spore doses and ranged from 3 to 7 days; potatoes inoculated with 10 spores were toxic after 5 to 7 days. Total toxin in individual potatoes incubated 3 to 5 days were 5 × 103 to 5 × 105 mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Electromyography can also be helpful in a foil-wrapped potato [11]. The foil retains the moisture, which means that the temperature at the surface of the potato does distinguishing botulism from other diseases, such as myasthenia gravis and Guillain-Barré syndrome, which may present with not exceed 100ЊC until all the moisture has evaporated, at which time the potato begins to scald or burn [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromyography can also be helpful in a foil-wrapped potato [11]. The foil retains the moisture, which means that the temperature at the surface of the potato does distinguishing botulism from other diseases, such as myasthenia gravis and Guillain-Barré syndrome, which may present with not exceed 100ЊC until all the moisture has evaporated, at which time the potato begins to scald or burn [13].…”
Section: Resultsmentioning
confidence: 99%
“…Individual differences in susceptibility to the toxin seems likely. are often present on the surface of raw potatoes [11]. Spores are killed if they are held at ú120ЊC for 20 min [12].…”
Section: Resultsmentioning
confidence: 99%
“…The detection of an allochthonous microbe, with no other known pathogen present in the stools of a diarrhea patient, has at times been sufficient to incriminate an organism as causative or to initiate the search for virulence factors. For example, a microaerophilic bacterium resembling Campylobacter was incriminated as a cause of chronic, mild gastroenteritis in two patients because it was present in patient stools and no other pathogens could be found (201 (239). In followrup studies, potatoes inoculated with varying numbers of Clostridium botulinum spores were baked and permitted to remain at 22 or 30TC for various time periods.…”
Section: Incriminated Gram-negative Bacteriamentioning
confidence: 99%
“…C. botulinum is commonly found in the soil, and its spores have been found on raw potatoes (5). Several outbreaks of botulism caused by eating potatoes have occurred in the United States (6)(7)(8), and laboratory studies have shown that C. botulinum spores on the surface of raw potatoes can survive baking and lead to production of botulinum toxin (5). The warm anaerobic fermentation process of making pruno probably predisposes toward production of botulinum toxin, particularly if any ingredient happens to be contaminated with C. botulinum or its spores, such as the potatoes used in these 2 instances.…”
Section: Discussionmentioning
confidence: 99%